COVID-19 disrupted provision and utilization of health and nutrition services in Uttar Pradesh, India: Insights from service providers, household phone surveys, and administrative data - Nguyen, Phuong Hong; Kachwaha, Shivani; Pant, Anjali; Tran, Lan Mai; Walia, Monika; Ghosh, Sebanti; Sharma, Praveen Kumar; Escobar-Alegria, Jessica; Frongillo, Edward A.; Menon, Purnima; Avula, Rasmi (Oxford University Press, 2021)
Background: The coronavirus (COVID-19) pandemic may substantially affect health systems, but little primary evidence is available on disruption of health and nutrition services. Objectives: This study aimed to 1) determine the extent of disruption in provision and utilization of health and nutrition services induced by the pandemic in Uttar Pradesh, India; and 2) identify how adaptations were made to restore service provision in response to the pandemic. Methods: We conducted longitudinal surveys with frontline workers (FLWs, n = 313) and mothers of children <2 y old (n = 659) in December 2019 (in-person) and July 2020 (by phone). We also interviewed block-level managers and obtained administrative data. We examined changes in service provision and utilization using Wilcoxon matched-pairs signed-rank tests. Results: Compared with prepandemic, service provision reduced substantially during lockdown (83–98 percentage points, pp), except for home visits and take-home rations (∼30%). Most FLWs (68%–90%) restored service provision in July 2020, except for immunization and hot cooked meals (<10%). Administrative data showed similar patterns of disruption and restoration. FLW fears, increased workload, inadequate personal protective equipment (PPE), and manpower shortages challenged service provision. Key adaptations made to provide services were delivering services to beneficiary homes (∼40%–90%), social distancing (80%), and using PPE (40%–50%) and telephones for communication (∼20%). On the demand side, service utilization reduced substantially (40–80 pp) during the lockdown, but about half of mothers received home visits and food supplementation. Utilization for most services did not improve after the lockdown, bearing the challenges of limited travel (30%), nonavailability of services (26%), and fear of catching the virus when leaving the house (22%) or meeting service providers (14%). Conclusions: COVID-19 disrupted the provision and use of health and nutrition services in Uttar Pradesh, India, despite adaptations to restore services. Strengthening logistical support, capacity enhancement, performance management, and demand creation are needed to improve service provision and utilization during and post-COVID-19.